Beyond Imaginative Geographies? Critique, cooptation and imagination in the aftermath of the War on Terror - Angharad Closs Stephens (Environment and Planning D: Society and Space, 2011)
This paper considers the question of what it might mean to resist the ‘imaginative geographies’ of the War on Terror through a reading of the bestselling novel The Reluctant Fundamentalist by Mohsin Hamid. Reading this novel against the claim that we are now at the ‘end’ of the War on Terror, the paper engages with how we might move beyond what Derek Gregory described as the split geographies of ‘us’ and ‘them’, ‘civilization’ and ‘barbarism’ that represent the violent return of the colonial past. The paper argues that critical attempts at resisting the imaginative geographies of the War on Terror, such as we find in this particular novel, often assume and reproduce an understanding of time as linear and progressive, an idea of time which Gregory points out makes these imaginative geographies possible. The paper argues that this becomes problematic when critical interventions risk reproducing the very understanding of political life that they set out to confront. Whilst it is an important political move to reveal the imaginative geographies at work in the War on Terror, the paper suggests that this approach also risks operating by confirming to a critical readership that which it already knows. We are too easily led to the conclusion that what is needed is better representations of ‘others’ in the world, as just as enlightened, cultured, reasoned as ‘us’. The contention of this paper is that such critical responses fail to do anything to disrupt or trouble the split geographies of ‘us’ and ‘them’; rather, they keep them firmly in place and entrench them further. The paper argues that we need to revisit and unsettle the concept of imagination at work in the idea of ‘imaginative geographies’ to explore a way of thinking coexistence in world politics that cannot be understood within a unifying temporal framework. It is suggested that, despite the closures identified in this novel, postcolonial urban literatures also provide many openings for thinking the “possibility that the field of the political is constitutively not singular” [Chakrabarty, 2000, Provincializing Europe (Princeton University Press, Princeton, NJ) page 148].